Decadal scale patterns of shoreline variability in Paulatuk, N.W.T, Canada. (3rd July 2019) - Sankar, Ravi Darwin; Murray, Maribeth S; Wells, Patricia
ABSTRACT: Dynamic changes in shoreline position as a result of natural processes and the effects of climate variability increase the susceptibility of Arctic communities that reside along the coastal zone. The application of new geospatial approaches is critical to providing updated measurements of shoreline change, necessary for sustainable coastal management strategies. This research is an integration of geographic data demarcating shoreline position and its analysis to detect change using an updated modeling application – Analyzing Moving Boundaries Using R (AMBUR). Rates-of-change were evaluated over three time periods: long-term (1984–2016); and two short-term eras (1995–2005; 2006–2016). The short-term periods were specifically chosen to assess the influence of changing sea-ice regimes, increased storm intensity, and elevated air and sea-surface temperatures. Results indicate a significant alongshore increase in the rates of erosion and the spatial extent of land loss across both segments of the study area over the short-term. Mean annual rates of change increased over the most recent period (2006–2016) along the eastern segment (−0.34 m/yr) of the study area, while the western shoreline retreated at a rate of −0.24 m/yr over the same interval. These are the highest erosion rates over any time period examined in this study. As air and ocean temperature increases continue to facilitate sea ice reduction and increased permafrost thawing, shoreline erosion may be exacerbated along the Paulatuk coastline in the coming years.